Pemberdayaan Guru Sekolah Dasar Melalui Pelatihan Literasi Digitial untuk Meningkatkan Kualitas Pembelajaran di Era Merdeka Belajar - Saputro, Nuha Eko; Angrraeni, Lutfiana (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The demand for digital literacy among elementary school teachers has heightened as part of Indonesia's Merdeka Belajar policy, where the teachers are required to be sensitive to change in the wake of new technology. Teachers cannot use digital tools effectively, particularly the application of technology in pedagogies, hence empowerment programs become essential. The objective of this community service study was to provide digital literacy training to augment teachers' technical and pedagogic competence. Thirty purposively selected teachers underwent a series of pre-test, training workshops and sessions, and post-test, founded on observation, reflection, and interview. The results indicated enhanced overall digital literacy scores for teachers by 26.4%, with the highest growth being in constructing digital learning media (34.2%). Besides this, training impacted positive attitudes and motivation, and also developed the construction of professional learning communities among teachers. The implications of these findings highlight the importance of digital literacy empowerment as a viable and scalable mechanism to support teacher preparedness and facilitate effective implementation of independent learning.